Recent Development of Alternating Current Field Measurement Combine with New Technology - Yuan, Xin'an.; Li, Wei.; Zhao, Jianming; Yin, Xiaokang; Li, Xiao.; Zhao, Jianchao; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book can be divided into three parts. In part 1, three articles are employed to introduce the RACFM technology. In part 2, two articles are introduced to explain the Multifrequency ACFM. In part 3, three articles are introduced to explain the visualization research in ACFM. With the development of ACFM detection technology, traditional single excitation frequency and single direction excitation structures cannot meet the requirements of multiple types of defect detection (such as cracks at different angles, and buried defects). New types of excitation structures and methods have been proposed, mainly including rotating electromagnetic field detection, multi-frequency detection, and defects visual algorithm. The changes in the excitation structure and signal mentioned above have expanded the scope of application of ACFM detection and provided opportunities for the cross-integration and innovation of ACFM detection technology with other advanced detection methods. This book mainly focuses on the study of the rotating alternating current field measurement (RACFM), the multifrequency ACFM, and the visualization method in ACFM.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Engineering geology; Petrology; Geoengineering; Petrology